Collectivizing justice: Participatory witnessing, sense memory, and emotional communities. (June 2023) - Yang, Emilia
This article describes and analyzes the practices made possible by the temporary exhibition of AMA y No Olvida, Museum of Memory Against Impunity, a community and transmedia museum project in Nicaragua, in tandem with the embodied performances of the families of the victims of state violence and visitors during repression and a state of exception. I theorize how the witnessing performed by the audience surpasses the framework of memory museums for human rights with a participatory framework that uses activist and performative expressions. Participatory witnessing is made possible by expanding the exhibition into a performative and political space in which society at large can participate and witness the victims' struggle for justice through sharing intimate experiences of embodied pain and grief and demands for justice and reparations. Such witnessing then creates an emotional community with solidarity and a moral and political commitment that recognizes and centers the victims as active survivors, activists, and protagonists.